In vivo immunomodulatory effect of the lectin from edible mushroom Agaricus bisporus - Ditamo, Yanina (2016)
Lectins are glycan-binding proteins that are resistant to digestion in the gastrointestinal tract and enter intact to blood circulation. The aim of this study was to evaluate the influence of edible mushroom Agaricus bisporus lectin (ABL) on innate and adaptive immune responses as well as its effect in two different experimental pathologies that involve the immune system. ABL inhibited in vitro nitric oxide (NO) production by mouse peritoneal macrophages in response to the pro-inflammatory stimuli lipopolysaccharides (LPS). However, it did not modify the activity of arginase, showing that while ABL downregulates M1 activation, it does not affect M2 activation. ABL also inhibited mononuclear cell proliferation in response to mitogen Con A, or in a mixed lymphocyte reaction. During the in vivo studies, oral administration of ABL to BALB/c mice induced a marked inhibition of NO production by peritoneal macrophages after LPS stimuli. The influence of ABL on tumor growth was studied in BALB/c mice receiving daily oral doses of ABL and implanted with CT26 tumor cells. ABL treatment induced significantly higher rate of tumor growth when compared with control mice. On the other hand, oral ABL administration in Wistar rats induced a marked diminution of the incidence of the disease and the severity of the clinical signs of experimental autoimmune encephalomyelitis. We can conclude that ABL has an in vivo immunomodulatory effect reducing the innate and adaptive responses. This food lectin shows potential therapeutic application on control of inflammatory autoimmune pathologies.